1998
DOI: 10.1021/jo971186w
|View full text |Cite
|
Sign up to set email alerts
|

Formal Synthesis of 3-Deoxy-d-manno-2-Octulosonic Acid (KDO) via a Highly Double-Stereoselective Hetero Diels−Alder Reaction Directed by a (Salen)CoII Catalyst and Chiral Diene

Abstract: This paper presents a formal total synthesis of 3-deoxy-D-manno-2-octulosonic acid (KDO) based on a highly double-stereoselective hetero Diels-Alder reaction between an electron-rich diene and ethyl glyoxylate catalyzed by (Salen)Co(II) complex, a new catalyst for Diels-Alder reactions. A facial specific hydroboration followed by oxidative workup leads to a diol system with the trans-diequatorial arrangement of hydroxyl groups at the C-4 and C-5. Inversion of the configuration of the C-5 hydroxyl group in 12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…These con- formers have dihedral (torsion) angles around the C(38)ϪC(39) and C(88)ϪC(89) bonds of 68Ϫ70°, similar to (dienyl)(glyoxime)cobalt complexes we have reported previously. [14] The Co(1)ϪC(38) and Co(2)ϪC(88) distances of 1.962(9) Å and 2.007 (13) Å are also similar to those seen in the glyoxime ligand series. [14] In solution, we saw no 1 H NMR line broadening over a temperature range of 25 to Ϫ63°C.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…These con- formers have dihedral (torsion) angles around the C(38)ϪC(39) and C(88)ϪC(89) bonds of 68Ϫ70°, similar to (dienyl)(glyoxime)cobalt complexes we have reported previously. [14] The Co(1)ϪC(38) and Co(2)ϪC(88) distances of 1.962(9) Å and 2.007 (13) Å are also similar to those seen in the glyoxime ligand series. [14] In solution, we saw no 1 H NMR line broadening over a temperature range of 25 to Ϫ63°C.…”
Section: Resultsmentioning
confidence: 69%
“…[11] Jacobsen and co-workers have reported the use of these (salen)Co complexes as catalysts for enantioselective epoxide ring opening [12] and their use as hetero DielsϪAlder catalysts has been reported by Wu et al in 1998. [13] Scheme 1 Leung et al reported that they reduced the (salen)Co II complexes 2a, 2b with sodium amalgam and treated the corresponding anion with unspecified alkyl halides. [11] However, they could not isolate the presumably formed alkylation products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quadridentate Schiff base cobalt complexes have been widely studied, particularly as homogeneous catalysts, oxygen carriers, and models of compounds with biological function [1][2][3][4][5][6][7][8][9][10][11][12]. It is known that variation of the size and nature of the ligand can be responsible for changes in the coordination geometry around central metal ions.…”
Section: Introductionmentioning
confidence: 99%